Pajak Karbon sebagai Instrumen Kebijakan untuk Mendorong Transisi Energi dan Pertumbuhan Ekonomi yang Berkelanjutan - Soekarno, Galih Rakasiwi; Sundari, Sri; Boedoyo, M. Sidik; Sianipar, Leo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Energy transition and sustainable economic growth have become global priorities in addressing climate change. Carbon taxation has been recognized as one of the effective policy instruments in reducing carbon emissions and promoting the use of clean energy sources. However, the implementation and impact of carbon taxation are still subject to debate, particularly in the context of economic growth. Therefore, this research aims to investigate the role of carbon taxation in energy transition and economic growth, as well as identifying the associated benefits and challenges. The concept of carbon taxation and its impact on energy transformation are the main focus of this study. Within the concept of carbon taxation, the appropriate tax rate and effective design are crucial keys. Carbon taxation can provide economic incentives to reduce carbon emissions and encourage the use of clean energy sources. However, its implementation faces challenges such as uneven social impacts and international coordination. Case studies of countries adopting carbon taxation are also conducted to illustrate the real-life experiences and impacts of this policy. Carbon taxation has great potential in driving energy transition and sustainable economic growth. Through carbon emission reduction, increased utilization of clean energy, technological innovation, and revenue for investment, carbon taxation can bring significant benefits. However, challenges in implementation and international coordination need to be overcome. Inclusive supportive policies, proper tax design, and strong international cooperation are some recommendations to optimize the benefits of carbon taxation. Keywords: carbon taxation, energy transition, economic growth, carbon emissions, clean energy sources.